Tribological study on hybrid metal matrix composites for application in automotive sector. (27th February 2019) - Sangeethkumar, E; Jaikumar, M; Sridath, K M N; Ramanathan, V; Sathyamurthy, Ravishankar
Abstract: Composite materials are extensively being employed in the aerospace and automobile industries where they could have replaced conventional materials owing to their high strength/weight ratio. In this direction, research has been vigorous to help turn out composite materials of superior quality with enhanced capabilities. Hence, this paper presents an attempt at fabricating a Hybrid Metal Matrix Composite (HMMC) with Aluminium Alloy AA2219 reinforced with various weight fractions of Silicon Carbide (SiC), Aluminium Oxide (Al2 O3 ) and Wollastonite (CaSiO3 ) in varying proportions to achieve better wear properties and weight reduction for applications like cast iron disc brake rotor. A two-step Stir Casting process is selected to prepare the composites. L 4 Standard Orthogonal Array is used to determine the number of experiments that need to be conducted in order to study the impact of the reinforcement materials using interaction effect plots. Pin-on-Disc wear tests and hardness tests were carried out on all the samples and the effect of the reinforcements studied from the test data. SEM is carried out on the composition with the best wear behaviour.